The child`s ideal approach to sport - Collins, D.; MacNamara, A. (Talent development: A practitioner guide, 2018)
Dweck identified two sets of beliefs that people have about their own intelligence and suggested that these implicit beliefs provide a perspective which influences each individual`s view of the world. Individuals hold either an entity theory of intelligence (termed a `fixed mindset`) or an incremental theory of intelligence (termed a `growth mindset`). Research has repeatedly shown that a growth mindset fosters positive attitudes towards practice and learning, and leads to a hunger for feedback and a greater ability to deal with setbacks. This chapter provides coaches and parents with an understanding and practical guidelines about how to develop, refine and reinforce appropriate mindsets. Given that the ability to effectively cope with and adapt to challenges is an important element in the effective development of specific attention, this chapter explores how the effective use of challenge can develop the self-regulative skills that help talented athletes acquire and consolidate the required knowledge, skills and experiences during their `development` years that can subsequently aid their progression to elite levels of performance.